Explain the ‘Explain’ (International Journal of Engineering and Computer Science, 2017)
The ultimate objective and focus of IT Shops today is to bring down the cost of operations and to run the business efficiently. High cost element to maintain the application and database is measured using the measure called MIPS [millions of instructions per second] and is calculated based on MIPS usage by CPU. In this paper we investigate in detail the causes behind high usage of CPU and the ways in which the MIPS Usage can be curtailed and the cost for it. This paper deals with the universal database DB2 which runs on mainframe MVS operating system. As all the older legacy systems were developed on mainframe using COBOL & DB2 sub-systems, re-engineering the applications is needed to bring the cost down. This paper discusses various sub topics on why and how the MIPS can be brought down with no impact to the application and business. Programs written with poor readability in an unstructured manner and without cost consciousness are the key factors causing performance issues now-a-days. Optimizer, a component which decides the optimal access path to fetch data from database is based on statistical data captured in system tables. By adopting various approaches and disciplines outlined in this paper surely would guide application programmers to script their queries appropriately and as a result, organization’s objectives and goals can be met. In computing, optimization is the process of modifying a system to improve its efficiency where the system can be a single entity or a collection of entities.